2021
DOI: 10.1001/amajethics.2021.487
|View full text |Cite
|
Sign up to set email alerts
|

Historical Trauma and Descendants' Well-Being

Abstract: Because multiple Asian American and Pacific Islander (AAPI) communities in the United States have experienced historical trauma (HT), it is important to understand HT's impact on the well-being of members of subsequent generations. This article addresses intergenerational trauma transmission, focusing primarily on Japanese American and Southeast Asian American communities. Research on these groups illuminates strategies for future empirical investigations of intergenerational trauma in other AAPI populations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Importantly, this study is the only one of its kind to have a high proportion of American Indian or Alaska Native and Native Hawaiian or Pacific Islander respondents. These groups have suffered historical trauma [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ], and the findings of this study are reflective of the impact of that trauma on vaccine hesitancy. The literature shows that outreach and connection in the community by healthcare providers correlates to vaccine uptake [ 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 90%
“…Importantly, this study is the only one of its kind to have a high proportion of American Indian or Alaska Native and Native Hawaiian or Pacific Islander respondents. These groups have suffered historical trauma [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ], and the findings of this study are reflective of the impact of that trauma on vaccine hesitancy. The literature shows that outreach and connection in the community by healthcare providers correlates to vaccine uptake [ 67 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 90%
“…Children of immigrants and refugees from Southeast Asian countries may also face intergenerational impacts from trauma their parents and grandparents experienced before coming to the United States, including historical trauma from the Vietnam War and Cambodian genocide (Patel & Nagata, 2021). Research has shown that premigration traumas experienced by Asian immigrants and refugees can lead to lasting survivor guilt, social isolation, and psychological distress, and make it more challenging to overcome language barriers and find employment (Li, 2016; Li & Anderson, 2016).…”
Section: Southeast Asian American Youthmentioning
confidence: 99%